PERBANDINGAN KEKERASAN DAN STRUKTUR MIKRO PEGAS DAUN YANG MENGALAMI PROSES HEAT TREATMENT - Rudi Saputra; Estu Tyastomo (Bina Teknika, 2016)
Leaf spring is a component that functions to receive dynamic load and provide comfort in driving. Leaf springs are commonly used small public service vehicles and small commercial vehicles are deteriorated mechanical properties prior to the age limit of leaf springs. To restore the mechanical properties of the spring there will be a heat treatment that includes heat treatment of cooling (quenching) .From Hardness Vickers hardness test results on steel leaf springs are associated with an increase of hardness, on the condition of normal leaf spring steel without heat treatment hardness obtained average price of 325 , on the condition of the leaf spring steel with heat treatment at a temperature of 8000C with cooling oil obtained average price of 380, on the condition of the leaf spring steel with heat treatment at a temperature of 8000C with air cooling average price obtained - average of 339, from the test results of metallographic condition microstructure on the leaf spring normally with no warm-up run into the matrix pearlitic and at the side there sulfide / impurities formed by sulfur, the results of tests metallographic condition of microstructure on the leaf spring that is experiencing warming with quenching oil in the form of a matrix martensitic and at the edges of experience decarburization , austenitic microstructure form, the results of tests metallographic condition of microstructure on the leaf spring is warming by cooling the air in the form of a matrix perlitic middle and at the edges of experience decarburization micro-structure in the form of ferrite-pearlite.